2001
DOI: 10.1289/ehp.01109295
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to lead and induction of genetic damage.

Abstract: To investigate whether occupational exposure to lead is genotoxic, we evaluated data from 103 lead-exposed workers and 78 matched controls. These data correspond to three different sampling periods, and we measured genetic damage as increases in the frequency of binucleated cells with micronuclei (BNMN) in peripheral blood lymphocytes. The levels of exposure were determined according to the lead levels in blood. Clearly significant increases in BNMN were observed in the exposed groups when compared to the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 31 publications
4
28
1
Order By: Relevance
“…For instance, toxicological studies have shown a significant correlation between binucleated cells with MN and low to medium high blood lead level thus further reinforcing the importance of the nuclear abnormality found in this study as indicators of toxicological changes and exposure (Vaglenov et al, 2001). …”
Section: Discussionsupporting
confidence: 82%
“…For instance, toxicological studies have shown a significant correlation between binucleated cells with MN and low to medium high blood lead level thus further reinforcing the importance of the nuclear abnormality found in this study as indicators of toxicological changes and exposure (Vaglenov et al, 2001). …”
Section: Discussionsupporting
confidence: 82%
“…Our results are in line with earlier findings that occupational exposure even to low levels of lead as well as to levels not exceeding the permissible levels increases the risk of genetic damage. 17,18 We have observed also an inverse relationship between oxidative damage, measured as change in tail intensity, tail length, tail moment between FPG modification and standard comet assay, and antioxidative potential (TAS) in serum, and positive correlation between level of lipid peroxidation (TBARS) and levels of DNA damage (measured based on both comet method as well as based on 8-OHdG levels in urine). Those results confirm the relationship between a weakened antioxidative defence and oxidative stress induced by various factors, including Pb, and the effects of genotoxic, observed also by other authors.…”
Section: Discussionmentioning
confidence: 88%
“…However, since concurrent controls were not administered vitamins, and the exposed workers were not divided into vitamin-treated and untreated groups, the possibility that the reduction in micronuclei was unrelated to the treatment with vitamins could not be ruled out. In a subsequent study from the same investigators in which lead workers were stratified into four exposure levels, PbBs >25 ÎŒg/dL were associated with significant increases in micronuclei frequency (Vaglenov et al 2001). …”
Section: Genotoxic Effectsmentioning
confidence: 96%
“…2001; Forni et al 1976;Nordenson et al 1978;Vaglenov et al 1998Vaglenov et al , 2001. In vitro mutagenicity studies in microorganisms have yielded mostly negative results for lead, and additional studies of this type are unlikely to provide new key information.…”
Section: Health Effectsmentioning
confidence: 99%